Demineralization of Rajmahal Gondwana Coals by Bacteria: Revelations from X-Ray Diffraction (XRD) and Fourier Transform Infra Red (FTIR) Studies. Issue 5 (October 2015) - Singh, Asha Lata; Singh, Prakash K; Kumar, Aniruddha; Singh, Mahendra P
The present paper entails the results of the demineralization of the Rajmahal Gondwana coals of India with Pseudomonas mendocina strain B6-1 and its signatures revealed in the X-ray Diffraction (XRD) and Fourier transform infrared (FTIR) spectra. The XRD study reveals the reduction of pyrite phase in the coal samples after bacterial treatment due to bio-oxidation of pyrite and the appearance of few new phases of jarosite. Moreover, the intensity of jarosite peaks has been noticed to increase after the bacterial treatment. The FTIR spectra of the bacterial treated Rajmahal coal samples indicate shifting of the absorption peaks as compared to the control samples. The oxidation of pyrite due to the bacterial action and its conversion into jarosite is indicated by the stretching of OH bond at 630 cm −1 peak. While the bacterial action on clay minerals in all the samples is indicated by the stretching of bonds at 1114 cm −1 to 430 cm −1 peaks.